Formulasi Bumbu Kari Instan Khas Indonesia Berbentuk Blok dengan Perbedaan Komposisi Tepung Pati Termodifikasi dan Tepung Terigu - Julia Kusumaningrum; Mardiah Mardiah; Aji Jumiono; Lia Amalia (JURNAL AGROINDUSTRI HALAL, 2024)
Curry is a typical Indonesian dish that requires a long process to make. Therefore, innovation in making curry in block form is needed, as has been done for Japanese curry blocks. This research aims to obtain the best curry block formulation based on sensory quality tests, hedonic tests, and chemical analysis. The research was carried out by formulating 5 formulas through trial and error (BK001, BK002, BK003, BK004, and BK005). The research treatment was the difference in ratio between modified starch and wheat flour, namely BK005A, BK005B, and BK005C. Data analysis used ANOVA and continued with Duncan at the 5% level. The trial and error stage research results showed that the best formulation was code BK 005. From the results of hedonic and sensory quality tests, BK 005 was preferred compared to curry seasoning on the market. The results of further research showed that the research treatment had a significant effect on the results of the texture and block compactness tests as well as the hedonic test results as overall. BK 005B block curry seasoning is the best treatment based on the results of texture tests, sensory quality tests, cohesiveness parameters, and overall taste. The results of the curry seasoning analysis for block BK 005B were water content 2.17%, water activity (Aw) 0.49, viscosity 0.3 dPas/s3, hardness 981.0 gr/mm2, and pH 6.00.